Kajian Molekuler Kuskus (Famili Phalangeridae) di Penangkaran Desa Lumoli, Seram, Maluku Berdasarkan Urutan Gen ATP8 - Marthinus Usmany; Pieter Kakisina (JURNAL KAJIAN VETERINER, 2019)
The cuscus is an Australian animal (marsupial) which belongs to the Phalangeridae family and its distribution is limited in eastern Indonesia, Australia and Papua New Guinea. Through IUCN data, cuscus is categorized as endangered species, in CITES it is classified as Appendix II. The population of cuscus is decreasing due to the threat of deforestation, many are hunted for consumption, and are traded illegally. To overcome the above problems, it is necessary to conduct a comprehensive study of the study of cuscus genotypes in the hope that they can assist in future wildlife conservation efforts. The purpose of this study was to molecularly examine the types of living cuscus in captivity in Lumoli Village, West Seram Regency, Maluku. This research begins with the stages of DNA isolation through cuscus tissue. DNA isolation products were amplified in the ATP 8 gene region by the PCR method, sequenced. Data was analyzed using MEGA program version 5.1. The PCR reaction produces 681 bp of product. The results of the analysis obtained 85 different nucleotide sites. The nucleotide sequence of the ATP 8 gene was analyzed using kimura 2 parameters. The construction of the filogram using the neighbor joining method with a bootstrap value 1000 times based on the ATP 8 gene sequence shows the kinship between the four types of cuscus, which produces two branches of Phalanger and Spilocuscus, namely brown cuscus related to white cuscus and related cuscus with spotted cuskus.